What is the protective effect of metformin on rat ovary against ischemia‐reperfusion injury?. Issue 2 (16th November 2017) - Dayangan Sayan, Cemile; Karaca, Gokhan; Sema Ozkan, Zehra; Tulmac, Ozlem B.; Ceylan Isik, Aslı; Devrim, Tuba; Aydin, Gülcin; Yeral, Ilkin
Abstract: Aim: The aim of this study was to investigate the protective effect of metformin on the rat ovary against ischemia‐reperfusion injury. Methods: Thirty‐seven female Wistar albino rats were used in the study. The rats were divided into five groups, as follows: sham operation group (group 1); torsion group (group 2); torsion/detorsion + saline group (group 3); torsion/detorsion + low‐dose metformin group (group 4); and torsion/detorsion + high‐dose metformin group (group 5). The right ovary from each rat was evaluated histologically using hematoxylin–eosin staining, and the left ovaries were evaluated for tissue levels of the reduced‐glutathione‐to‐oxidized‐glutathione ratio, malondialdehyde (MDA), and caspase‐3 activation. Results: The highest damage score was observed in group 3, and the lowest score was observed in group 1. The tissue caspase‐3 activity levels of groups 2, 3, and 4 were significantly higher than those of group 1. The difference between group 1 and group 5 in terms of tissue caspase‐3 activity was not significant ( P = 0.4). The reduced‐glutathione‐to‐oxidized‐glutathione ratio of group 1 was significantly higher than the ratios found in groups 2, 3, and 4. The tissue MDA level of group 1 was significantly lower than the levels found in groups 2, 3, 4, and 5. The tissue MDA level of group 5 was significantly lower than the levels in groups 3 and 4. Conclusion: From both histopathological and biochemical analyses, the results of the study demonstrated that metformin has beneficial effects when it comes to attenuating ovarian ischemia‐reperfusion injury.